A method for preparing silicon carbide ceramics using silicon carbide solid waste

CN122940460APending Publication Date: 2026-10-20SHAANXI UDC MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611433148.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-16
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

通过喷雾造粒、压制成形、二次脱胶和烧结过程,可将碳化硅素坯废料重新转化为具有实用价值的碳化硅陶瓷制品,从而解决现有回收方法中废料利用率低、烧结致密化不足、成形稳定性差和生产成本较高的问题

Benefits of technology

(1)本发明以碳化硅素坯废料作为主要原料,经破碎形成破碎后的碳化硅素坯废料,再依次进行预脱胶处理和脱胶处理,使碳化硅素坯废料中残留的有机助剂逐步排出,减少后续烧结过程中因有机残留分解导致的孔隙、开裂和局部收缩异常。脱胶碳化硅废料经粉碎、分级后形成碳化硅粉体,碳化硅粉体经磁选后得到再生碳化硅粉料,可降低铁磁性杂质对烧结过程和晶界结构的影响,提高碳化硅固体废料的回收利用率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention discloses a method for preparing silicon carbide ceramics using silicon carbide solid waste in the field of ceramic material resource utilization technology. The method involves crushing silicon carbide raw material waste, followed by pre-degumming and degumming treatments, and then pulverizing, classifying, and magnetically separating to obtain recycled silicon carbide powder. The recycled silicon carbide powder is then ball-milled with a carbon-boron-aluminum-yttrium composite sintering aid precursor, boron carbide powder, water-soluble phenolic resin, ammonium polyacrylate, and deionized water to form a slurry. This slurry is then spray-granulated, pressed, degummed again, and sintered to obtain silicon carbide ceramics. This method can improve the recycling rate of silicon carbide solid waste, improve sintering density and forming stability, and reduce raw material waste and production costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ceramic material resource utilization technology, specifically relating to a method for preparing silicon carbide ceramics using silicon carbide solid waste. Background Technology

[0002] Silicon carbide ceramics are characterized by high hardness, good wear resistance, strong corrosion resistance, excellent high-temperature resistance, and good thermal stability. They are widely used in mechanical seals, wear-resistant bushings, nozzles, kiln furniture, heat exchange components, semiconductor thermal field components, and chemical corrosion-resistant structural parts. With the increasing demand for silicon carbide ceramic products, the amount of silicon carbide green body scraps, pressing residues, broken green bodies, and powder recycling materials generated during production is also increasing. These solid wastes, before sintering, still primarily consist of silicon carbide and have high resource utilization value. However, they often contain binders, dispersants, lubricants, resin additives, and small amounts of processing-introduced impurities. If directly recycled for ceramic preparation, they can easily cause uneven slurry dispersion, powder agglomeration, fluctuations in green body density, and increased sintering defects, affecting the density and mechanical properties of the final ceramic products.

[0003] Current methods for treating silicon carbide solid waste primarily involve simple crushing, screening, or low-value filling. Some companies even treat it directly as general solid waste, which not only wastes high-value silicon carbide resources but also increases environmental governance and production costs. For silicon carbide green body waste, if residual organic additives are not fully removed, they can decompose, volatilize, or cause uneven carbon residue during subsequent heating, leading to porosity, black core, cracking, and abnormal local shrinkage within the green body. Simultaneously, the particle size distribution of the recovered powder after crushing is often unstable, with oxide layers and fine agglomerates on the particle surface. Without appropriate powder activation, dispersion, and sintering aids, it is difficult to obtain granulated powder with good flowability and to form a uniform and dense silicon carbide ceramic structure under conventional sintering conditions.

[0004] To improve the resource utilization level of silicon carbide solid waste, a recycling method that balances low cost, process adaptability, and sintering stability is needed. This method should first remove residual organic additives from the raw blank waste through pre-degumming and degumming treatments. Then, through crushing, grading, and magnetic separation, recycled silicon carbide powder with relatively stable particle size and fewer impurities is obtained. Furthermore, composite sintering aid precursors, boron carbide powder, water-soluble phenolic resin, and dispersants are used to improve the powder's sintering activity, slurry dispersibility, and granulation performance. Through spray granulation, pressing, secondary degumming, and sintering processes, silicon carbide raw blank waste can be transformed back into silicon carbide ceramic products with practical value, thereby solving the problems of low waste utilization, insufficient sintering densification, poor forming stability, and high production costs in existing recycling methods. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing silicon carbide ceramics using silicon carbide solid waste.

[0006] A first aspect of the present invention provides a method for preparing silicon carbide ceramics using silicon carbide solid waste, comprising the following steps: S1. By weight, 490-510 parts of silicon carbide blank waste are crushed to obtain crushed silicon carbide blank waste; the crushed silicon carbide blank waste is placed in a heat treatment furnace and pre-degummed under air atmosphere, followed by degumming under nitrogen atmosphere, and naturally cooled to room temperature to obtain degummed silicon carbide waste.

[0007] S2. Crush and classify the degummed silicon carbide waste to obtain silicon carbide powder; magnetically separate the silicon carbide powder to obtain recycled silicon carbide powder.

[0008] S3. Add 85-95 parts of recycled silicon carbide powder, 1.0-3.0 parts of carbon-boron-aluminum-yttrium composite sintering aid precursor, 0.3-0.8 parts of boron carbide powder, 1.5-3.5 parts of water-soluble phenolic resin, 0.2-0.5 parts of ammonium polyacrylate and 45-60 parts of deionized water to a ball mill, ball mill, filter, and obtain silicon carbide ceramic slurry.

[0009] S4. Spray granulation of silicon carbide ceramic slurry to obtain silicon carbide granulated powder; press silicon carbide granulated powder into shape to obtain a shaped green body; perform secondary debinding treatment on the shaped green body under nitrogen atmosphere, and then sinter it in argon atmosphere and cool it naturally to room temperature.

[0010] In this invention, the method for preparing silicon carbide ceramics using silicon carbide solid waste involves crushing the silicon carbide preform waste. This increases the heat-receiving interface of the residual organic additives and agglomerated regions, which is beneficial for heat conduction and gaseous product discharge during subsequent degumming treatment, resulting in crushed silicon carbide preform waste. During pre-degumming treatment in air, easily decomposable and volatile organic residues preferentially undergo oxidative decomposition at low temperatures and are discharged in gaseous form. Subsequently, degumming is performed under nitrogen atmosphere, where residual organic components undergo thermal decomposition in an inert environment, preventing excessive oxidation of the silicon carbide surface during higher-temperature treatment, resulting in degummed silicon carbide waste. After crushing and grading, the degummed silicon carbide waste is transformed from lumpy material into silicon carbide powder with a concentrated particle size distribution, and coarse agglomerates are deagglomerated. After magnetic separation, ferromagnetic impurities introduced during the crushing process are separated, yielding regenerated silicon carbide powder. When recycled silicon carbide powder is mixed with a carbon-boron-aluminum-yttrium composite sintering aid precursor, boron carbide powder, water-soluble phenolic resin, ammonium polyacrylate, and deionized water in a ball mill, the ammonium polyacrylate adsorbs on the surface of the recycled silicon carbide powder particles, generating electrostatic repulsion and reducing the tendency of particle agglomeration. The water-soluble phenolic resin acts as a binder component distributed in the interparticle gaps, while also providing a source of residual carbon for the subsequent secondary degumming stage. The carbon-boron-aluminum-yttrium composite sintering aid precursor and boron carbide powder are distributed on the surface and interparticle gaps of the recycled silicon carbide powder particles. After filtration, a silicon carbide ceramic slurry is formed. The silicon carbide ceramic slurry is spray-granulated to form silicon carbide granulated powder with uniform particle size and good flowability. The silicon carbide granulated powder is then pressed into a green body with a certain green strength. During the secondary degumming treatment of the formed green body under a nitrogen atmosphere, the water-soluble phenolic resin undergoes thermal decomposition. Some of the organic structure is discharged as gaseous products, while the remainder is converted into residual carbon in situ and retained in the green body, providing a reactive carbon source for the subsequent sintering stage. Subsequently, during sintering in an argon atmosphere, the residual carbon formed by the decomposition of boron carbide powder and water-soluble phenolic resin undergoes a reduction reaction with the oxide layer on the surface of the recycled silicon carbide powder particles, reducing the oxygen content on the particle surface. The yttrium-containing, aluminum-containing, and boron-containing components in the carbon-boron-aluminum-yttrium composite sintering aid precursor form a liquid phase at high temperature, which is distributed at the grain boundaries of the recycled silicon carbide powder, promoting material migration at the particle boundaries, growth of contact necks between particles, and pore discharge, thereby gradually densifying the formed green body to obtain silicon carbide ceramics.

[0011] According to a preferred embodiment of the present invention, in step S1, the particle size of the crushed silicon carbide blank waste is 5-20 mm.

[0012] According to a preferred embodiment of the present invention, in step S1, the temperature of the pre-degumming treatment is 450-520°C, and the temperature of the degumming treatment is 750-850°C.

[0013] According to a preferred embodiment of the present invention, in step S2, the D50 of the regenerated silicon carbide powder is 1.0-3.5 μm.

[0014] According to a preferred embodiment of the present invention, in step S4, the temperature of the secondary degumming treatment is 500-650°C, and the sintering temperature is 2050-2150°C.

[0015] According to a preferred embodiment of the present invention, the preparation steps of the carbon-boron-aluminum-yttrium composite sintering aid precursor include: A1. By weight, add 18.0-22.0 parts of yttrium hexahydrate, 26.0-30.0 parts of aluminum nitrate nonahydrate, 8.0-12.0 parts of boric acid and 18.0-24.0 parts of citric acid monohydrate to a reactor, add 120-150 parts of deionized water, and stir at 55-65℃; then add 6.0-10.0 parts of glucose monohydrate and continue stirring; add ammonia water to adjust the pH to obtain a yttrium aluminum boron citric acid complex solution.

[0016] A2. Cool the yttrium aluminum boron citric acid complex solution, add 80-110 parts of anhydrous ethanol dropwise, and continue stirring to obtain a gel precipitation system; allow the gel precipitation system to stand and age, filter, and obtain a wet precipitate; wash the wet precipitate with anhydrous ethanol to obtain a wet carbon boron aluminum yttrium composite precursor.

[0017] A3. The wet carbon-boron-aluminum-yttrium composite precursor is dried at 80-90℃ to obtain a dried precursor; the dried precursor is crushed and sieved to obtain precursor powder; the precursor powder is placed in a tube furnace and heated to 320-380℃ under a nitrogen atmosphere, and then naturally cooled to room temperature to obtain a carbon-containing intermediate powder.

[0018] A4. Place the carbon-containing intermediate powder in a tube furnace and heat it to 620-700℃ under an argon atmosphere. Then, allow it to cool naturally to room temperature to obtain the activated product. Ball mill the activated product and sieve it.

[0019] In this invention, during the preparation of the carbon-boron-aluminum-yttrium composite sintering aid precursor, yttrium hexahydrate and aluminum nonahydrate are dissolved in deionized water, providing yttrium and aluminum sources, respectively; boric acid dissolves in the aqueous phase to form a boron-containing component. After dissolving citric acid monohydrate, its carboxyl groups coordinate with the metal ions generated by the ionization of yttrium hexahydrate and aluminum nonahydrate in the aqueous phase, forming a citric acid complex system with yttrium and aluminum as coordination centers. This allows the yttrium and aluminum sources to disperse in the aqueous phase as complexes, inhibiting local hydrolysis precipitation and component segregation. Under the aforementioned acid-base conditions, boric acid is mainly distributed in molecular form in the solution, providing a source of boron for the subsequent heat treatment stage. Glucose monohydrate, after dissolving, disperses in the solution, serving as a carbon source for subsequent thermal decomposition to form a carbon-containing structure. After adjusting the pH of the system with ammonia, the carboxyl groups of citric acid monohydrate are further deprotonated, enhancing its coordination ability with yttrium and aluminum sources. Yttrium nitrate hexahydrate, aluminum nitrate nonahydrate, boric acid, and glucose monohydrate form a uniformly distributed yttrium aluminum boron citric acid complex solution in the aqueous phase. Upon cooling the yttrium aluminum boron citric acid complex solution, anhydrous ethanol is added dropwise. The solvent polarity decreases, the solubility of the metal citric acid complex decreases, and it precipitates. Boric acid and glucose monohydrate are entrained in the precipitated complex framework, forming a gel-like precipitate. After static aging, the complex framework cross-links and shrinks. Filtration yields a wet precipitate. Washing with anhydrous ethanol removes residual soluble components and free water from the surface, yielding a wet carbon-containing boron aluminum yttrium composite precursor. After drying, the free water and water of crystallization in the complex framework of the wet carbon-boron-aluminum-yttrium composite precursor are removed, yielding a dried precursor. This dried precursor is then crushed and sieved to obtain precursor powder. During heating in a nitrogen atmosphere, citric acid monohydrate and glucose monohydrate undergo dehydration, condensation, and thermal decomposition, while nitrate decomposes to release gaseous products. The yttrium source, aluminum source, and boron-containing components are transformed into an amorphous oxygen-containing inorganic phase, and the organic residues form a carbon-containing structure in situ, yielding a carbon-containing intermediate powder. Further heating in an argon atmosphere causes further cracking and carbonization of the residual organic components. The oxygen-containing inorganic phase and the carbon-containing structure form a composite distribution of activated products in the solid phase. After ball milling and sieving, the particle size and distribution of the activated products are controlled, yielding a carbon-boron-aluminum-yttrium composite sintering aid precursor.

[0020] According to a preferred embodiment of the present invention, in step A1, the pH is adjusted to 5.0-5.4.

[0021] According to a preferred embodiment of the present invention, in step A2, the yttrium aluminum boron citric acid complex solution is cooled to 35-40°C; and the aging time is 6-10 hours.

[0022] According to a preferred embodiment of the present invention, in step A3, the time for heating to 320-380°C is 1.0-1.5 hours.

[0023] According to a preferred embodiment of the present invention, in step A4, the time for heating to 620-700°C is 1.5-2.5 hours.

[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention uses silicon carbide blank waste as the main raw material. After crushing, the silicon carbide blank waste is subjected to pre-degumming and degumming treatments in sequence, so that the residual organic additives in the silicon carbide blank waste are gradually discharged, reducing the porosity, cracking and local shrinkage abnormalities caused by the decomposition of organic residues during subsequent sintering. The degummed silicon carbide waste is crushed and classified to form silicon carbide powder. The silicon carbide powder is then magnetically separated to obtain recycled silicon carbide powder, which can reduce the influence of ferromagnetic impurities on the sintering process and grain boundary structure, and improve the recycling rate of silicon carbide solid waste.

[0025] (2) In this invention, recycled silicon carbide powder, a carbon-boron-aluminum-yttrium composite sintering aid precursor, boron carbide powder, water-soluble phenolic resin, ammonium polyacrylate, and deionized water are ball-milled together to form a silicon carbide ceramic slurry. Ammonium polyacrylate helps reduce the agglomeration tendency between recycled silicon carbide powder particles, while water-soluble phenolic resin helps improve the slurry's bonding properties and forms a carbon-containing structure after secondary degumming treatment. The carbon-boron-aluminum-yttrium composite sintering aid precursor and boron carbide powder are distributed on the surface of the recycled silicon carbide powder particles and in the interparticle spaces, which is beneficial for the migration of boundary materials and the discharge of pores during the subsequent sintering process.

[0026] (3) In this invention, silicon carbide ceramic slurry is spray-granulated to obtain silicon carbide granulated powder, which is then pressed into a green body, thereby improving the powder filling state and the density distribution of the green body. The green body undergoes a secondary debinding treatment under a nitrogen atmosphere, which can reduce the oxidation and consumption of carbon-containing structures. Subsequently, sintering is carried out under an argon atmosphere. The carbon-boron-aluminum-yttrium composite sintering aid precursor, boron carbide powder, and carbon-containing structures formed by the thermal decomposition of water-soluble phenolic resin jointly participate in the sintering densification process, thereby improving the densification, forming stability, and resource utilization effect of silicon carbide ceramics. Detailed Implementation

[0027] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.

[0028] Example 1

[0029] This embodiment provides a method for preparing silicon carbide ceramics using silicon carbide solid waste, including the following steps: S1. Crush 500g of silicon carbide blank waste, and control the particle size of the crushed silicon carbide blank waste to be 12.5mm to obtain crushed silicon carbide blank waste; place the crushed silicon carbide blank waste in a heat treatment furnace, and perform pre-degumming treatment at 485℃ for 3h in an air atmosphere, followed by degumming treatment at 800℃ for 1.5h in a nitrogen atmosphere, and naturally cool to room temperature to obtain degummed silicon carbide waste.

[0030] S2. The degummed silicon carbide waste is pulverized and classified by air jet milling to obtain silicon carbide powder; the silicon carbide powder is magnetically separated under a magnetic induction intensity of 0.8T to obtain recycled silicon carbide powder with a D50 of 2.25μm.

[0031] S3. Add 90g of recycled silicon carbide powder, 2.0g of carbon boron aluminum yttrium composite sintering aid precursor, 0.55g of boron carbide powder, 2.5g of water-soluble phenolic resin, 0.35g of ammonium polyacrylate and 52.5g of deionized water into a ball mill and ball mill for 12 hours to mix and disperse the recycled silicon carbide powder, carbon boron aluminum yttrium composite sintering aid precursor, boron carbide powder, water-soluble phenolic resin and ammonium polyacrylate in deionized water. Filter to obtain silicon carbide ceramic slurry.

[0032] S4. Spray granulation of silicon carbide ceramic slurry, controlling the inlet air temperature to 200℃ and the outlet air temperature to 90℃, to obtain silicon carbide granulated powder; press the silicon carbide granulated powder into shape at 150MPa to obtain a shaped green body; under a nitrogen atmosphere, perform a secondary debinding treatment at 575℃ for 2h, then place it in an argon atmosphere and sinter at 2100℃ for 2h, and naturally cool to room temperature to obtain silicon carbide ceramic.

[0033] Preparation steps of carbon-boron-aluminum-yttrium composite sintering aid precursor: A1. Add 20.0g of yttrium hexahydrate, 28.0g of aluminum nitrate nonahydrate, 10.0g of boric acid and 21.0g of citric acid monohydrate to a reactor, add 135g of deionized water, and stir at 60℃ for 45min to dissolve the yttrium hexahydrate, aluminum nitrate nonahydrate, boric acid and citric acid monohydrate; then add 8.0g of glucose monohydrate and continue stirring for 1.5h to disperse the glucose monohydrate in the system; add 13.0g of ammonia water to adjust the pH to 5.2 to obtain a yttrium aluminum boron citric acid complex solution.

[0034] A2. Cool the yttrium aluminum boron citric acid complex solution to 37.5℃, add 95g of anhydrous ethanol dropwise over 30min, and continue stirring for 45min to obtain a gel precipitation system; allow the gel precipitation system to stand and age for 8h, filter to obtain a wet precipitate; wash the wet precipitate with 20g of anhydrous ethanol to obtain a wet carbon boron aluminum yttrium composite precursor.

[0035] A3. The wet carbon-boron-aluminum-yttrium composite precursor was dried at 85°C for 8 hours to obtain a dried precursor. The dried precursor was crushed and passed through a sieve with a mesh size of 150 μm to obtain precursor powder. The precursor powder was placed in a tube furnace and heated to 350°C for 1.25 hours under a nitrogen atmosphere, and then naturally cooled to room temperature to obtain a carbon-containing intermediate powder.

[0036] A4. The carbon-containing intermediate powder was placed in a tube furnace and heated to 660℃ for 2.0 h under an argon atmosphere. It was then naturally cooled to room temperature to obtain the activated product. The activated product was ball-milled for 2 h and passed through a sieve with a mesh size of 75 μm to obtain a carbon-boron-aluminum-yttrium composite sintering aid precursor.

[0037] Example 2

[0038] The difference between this embodiment and Embodiment 1 is that this embodiment provides a method for preparing silicon carbide ceramics using silicon carbide solid waste, including the following steps: S1. Crush 490g of silicon carbide blank waste, and control the particle size of the crushed silicon carbide blank waste to be 5mm to obtain crushed silicon carbide blank waste; place the crushed silicon carbide blank waste in a heat treatment furnace, and perform pre-degumming treatment at 450℃ for 2h in an air atmosphere, followed by degumming treatment at 750℃ for 1h in a nitrogen atmosphere, and naturally cool to room temperature to obtain degummed silicon carbide waste.

[0039] S2. The degummed silicon carbide waste is pulverized and classified by air jet milling to obtain silicon carbide powder; the silicon carbide powder is magnetically separated under a magnetic induction intensity of 0.6T to obtain recycled silicon carbide powder with a D50 of 1.0μm.

[0040] S3. Add 85g of recycled silicon carbide powder, 1.0g of carbon boron aluminum yttrium composite sintering aid precursor, 0.3g of boron carbide powder, 1.5g of water-soluble phenolic resin, 0.2g of ammonium polyacrylate and 45g of deionized water into a ball mill and ball mill for 8 hours to mix and disperse the recycled silicon carbide powder, carbon boron aluminum yttrium composite sintering aid precursor, boron carbide powder, water-soluble phenolic resin and ammonium polyacrylate in deionized water. Filter to obtain silicon carbide ceramic slurry.

[0041] S4. Spray granulation of silicon carbide ceramic slurry, controlling the inlet air temperature to 180℃ and the outlet air temperature to 80℃, to obtain silicon carbide granulated powder; press the silicon carbide granulated powder into shape at 120MPa to obtain a shaped green body; under a nitrogen atmosphere, perform a secondary debinding treatment at 500℃ for 1h, then place it in an argon atmosphere and sinter at 2050℃ for 1.5h, and naturally cool to room temperature to obtain silicon carbide ceramic.

[0042] Preparation steps of carbon-boron-aluminum-yttrium composite sintering aid precursor: A1. Add 18.0g of yttrium hexahydrate, 26.0g of aluminum nitrate nonahydrate, 8.0g of boric acid and 18.0g of citric acid monohydrate to a reactor, add 120g of deionized water, and stir at 55℃ for 30min to dissolve the yttrium hexahydrate, aluminum nitrate nonahydrate, boric acid and citric acid monohydrate; then add 6.0g of glucose monohydrate and continue stirring for 1.0h to disperse the glucose monohydrate in the system; add 10.0g of ammonia water to adjust the pH to 5.0 to obtain a yttrium aluminum boron citric acid complex solution.

[0043] A2. Cool the yttrium aluminum boron citric acid complex solution to 35°C, add 80g of anhydrous ethanol dropwise over 20 min, and continue stirring for 30 min to obtain a gel precipitation system; allow the gel precipitation system to stand and age for 6 h, filter, and obtain a wet precipitate; wash the wet precipitate with 18g of anhydrous ethanol to obtain a wet carbon boron aluminum yttrium composite precursor.

[0044] A3. The wet carbon-boron-aluminum-yttrium composite precursor was dried at 80°C for 6 hours to obtain a dried precursor. The dried precursor was crushed and passed through a sieve with a mesh size of 150 μm to obtain precursor powder. The precursor powder was placed in a tube furnace and heated to 320°C for 1 hour under a nitrogen atmosphere. It was then naturally cooled to room temperature to obtain a carbon-containing intermediate powder.

[0045] A4. The carbon-containing intermediate powder was placed in a tube furnace and heated to 620℃ for 1.5h under an argon atmosphere. It was then naturally cooled to room temperature to obtain the activated product. The activated product was ball-milled for 1.5h and passed through a sieve with a mesh size of 75μm to obtain a carbon-boron-aluminum-yttrium composite sintering aid precursor.

[0046] Example 3

[0047] The difference between this embodiment and Embodiment 1 is that this embodiment provides a method for preparing silicon carbide ceramics using silicon carbide solid waste, including the following steps: S1. Crush 510g of silicon carbide blank waste, and control the particle size of the crushed silicon carbide blank waste to be 20mm to obtain crushed silicon carbide blank waste; place the crushed silicon carbide blank waste in a heat treatment furnace, and perform pre-degumming treatment at 520℃ for 4h in an air atmosphere, followed by degumming treatment at 850℃ for 2h in a nitrogen atmosphere, and naturally cool to room temperature to obtain degummed silicon carbide waste.

[0048] S2. The degummed silicon carbide waste is pulverized and classified by air jet milling to obtain silicon carbide powder; the silicon carbide powder is magnetically separated under a magnetic induction intensity of 1.0T to obtain recycled silicon carbide powder with a D50 of 3.5μm.

[0049] S3. Add 95g of recycled silicon carbide powder, 3.0g of carbon boron aluminum yttrium composite sintering aid precursor, 0.8g of boron carbide powder, 3.5g of water-soluble phenolic resin, 0.5g of ammonium polyacrylate and 60g of deionized water into a ball mill and ball mill for 16h to mix and disperse the recycled silicon carbide powder, carbon boron aluminum yttrium composite sintering aid precursor, boron carbide powder, water-soluble phenolic resin and ammonium polyacrylate in deionized water, filter, and obtain silicon carbide ceramic slurry.

[0050] S4. Spray granulation of silicon carbide ceramic slurry, controlling the inlet air temperature to 220℃ and the outlet air temperature to 100℃, to obtain silicon carbide granulated powder; press the silicon carbide granulated powder into shape at 180MPa to obtain a shaped green body; under a nitrogen atmosphere, perform a secondary debinding treatment at 650℃ for 3h, then place it in an argon atmosphere and sinter at 2150℃ for 2.5h, and naturally cool to room temperature to obtain silicon carbide ceramic.

[0051] Preparation steps of carbon-boron-aluminum-yttrium composite sintering aid precursor: A1. Add 22.0g of yttrium hexahydrate, 30.0g of aluminum nitrate nonahydrate, 12.0g of boric acid and 24.0g of citric acid monohydrate to a reactor, add 150g of deionized water, and stir at 65℃ for 60min to dissolve the yttrium hexahydrate, aluminum nitrate nonahydrate, boric acid and citric acid monohydrate; then add 10.0g of glucose monohydrate and continue stirring for 2.0h to disperse the glucose monohydrate in the system; add 16.0g of ammonia water and adjust the pH to 5.4 to obtain a yttrium aluminum boron citric acid complex solution.

[0052] A2. Cool the yttrium aluminum boron citric acid complex solution to 40°C, add 110g of anhydrous ethanol dropwise over 40 min, and continue stirring for 60 min to obtain a gel precipitation system; allow the gel precipitation system to stand and age for 10 h, filter, and obtain a wet precipitate; wash the wet precipitate with 22g of anhydrous ethanol to obtain a wet carbon boron aluminum yttrium composite precursor.

[0053] A3. The wet carbon-boron-aluminum-yttrium composite precursor was dried at 90°C for 10 hours to obtain a dried precursor. The dried precursor was crushed and passed through a sieve with a mesh size of 150 μm to obtain precursor powder. The precursor powder was placed in a tube furnace and heated to 380°C for 1.5 hours under a nitrogen atmosphere. It was then naturally cooled to room temperature to obtain a carbon-containing intermediate powder.

[0054] A4. Place the carbon-containing intermediate powder in a tube furnace and heat it to 700℃ for 2.5h under an argon atmosphere. Then, let it cool naturally to room temperature to obtain the activated product. Ball mill the activated product for 2.5h and pass it through a sieve with a mesh size of 75μm to obtain the carbon-boron-aluminum-yttrium composite sintering aid precursor.

[0055] Comparative Example 1

[0056] The difference between this comparative example and Example 1 is that 2.0g of carbon boron aluminum yttrium composite sintering aid precursor is not added in step S3, while the rest is the same as in Example 1.

[0057] Comparative Example 2

[0058] The difference between this comparative example and Example 1 is that 0.55g of boron carbide powder is not added in step S3, while the rest is the same as in Example 1.

[0059] Comparative Example 3

[0060] The difference between this comparative example and Example 1 is that 2.0g of carbon boron aluminum yttrium composite sintering aid precursor and 0.55g of boron carbide powder are not added in step S3, while the rest is the same as in Example 1.

[0061] A series of standardized tests were conducted on the methods for preparing silicon carbide ceramics using silicon carbide solid waste as described in Examples 1-3 and Comparative Examples 1-3.

[0062] Silicon carbide ceramics prepared in Examples 1-3 and Comparative Examples 1-3 were used as test samples. Before testing, the sample surface was inspected, and samples with visible cracks, missing corners, and chipped edges were removed. The samples were then dried in a 110°C drying oven to constant weight and then cooled to room temperature in a desiccator.

[0063] For the bulk density and apparent porosity tests, the dried sample was weighed to obtain its dry mass. Then, the sample was placed in deionized water for vacuum saturation treatment to fully fill the open pores with water. After removing the sample, the surface water was wiped off, and the saturated mass was weighed. The sample was then suspended in deionized water and the suspended mass was weighed. The bulk density and apparent porosity were calculated based on the dry mass, saturated mass, suspended mass, and the density of deionized water at the test temperature. Five samples were tested in each group, and the average value was taken.

[0064] For the three-point bending strength test, the sample is processed into a long strip. The tensile surface of the sample is ground with a diamond wheel and the surface is cleaned. The edges of the sample are chamfered to avoid abnormal fracture caused by edge defects. The sample is placed on a three-point bending fixture with a support span of 30 mm. The loading head is located at the center of the span. The load is applied at 0.5 mm / min at room temperature. The maximum load when the sample breaks is recorded. The three-point bending strength is calculated based on the maximum load, support span, sample width and sample thickness. Five samples are tested in each group and the average value is taken.

[0065] During the Vickers hardness test, the test surface of the sample is ground, polished, and cleaned in sequence. The test surface must not have obvious scratches or chipped edges that would affect the indentation reading. The Vickers diamond indenter is used for the indentation test, with a test force of 98.07 N and a holding time of 15 s. At least 5 effective indentations are selected for each sample. The distance between indentations and from the indentation to the edge of the sample should not be less than 3 times the length of the diagonal of the indentation. The lengths of the two diagonals of the indentation are measured and the Vickers hardness is calculated. The average value of each group is taken.

[0066] During fracture toughness testing, the sample is processed into a single-sided pre-cracked beam specimen. A pre-crack is prepared on one side of the specimen and the crack length is measured. The crack tip is located in the middle of the tensile side of the specimen. The specimen is placed on a three-point bending fixture and loaded to fracture at room temperature. The fracture load is recorded, and the fracture toughness is calculated based on the specimen width, thickness, support span, pre-crack length, and fracture load. Five samples are tested in each group and the average value is taken.

[0067] During the room temperature abrasion resistance test, the test surface of the sample is ground flat and cleaned. Before the test, the initial mass is weighed. Silicon carbide abrasive of a specified particle size is sprayed onto the test surface of the sample under the action of compressed air. The spraying distance, spraying angle, spraying pressure and spraying time are kept consistent in the same group of tests. After the test, the residual abrasive on the sample surface is removed and the mass after wear is weighed. The wear volume is calculated based on the mass difference before and after wear and the sample bulk density. The wear rate is calculated according to the wear volume, load and sliding distance or equivalent wear conditions. Three samples are tested in each group and the average value is taken.

[0068] The performance test data above are shown in Table 1.

[0069] Table 1: Performance Test Results

[0070] As can be seen from the above, the bulk density of Examples 1-3 is 3.11-3.15 g / cm³. 3 It was significantly higher than the 2.94-3.06 g / cm³ of comparative examples 1-3. 3 The apparent porosity is 0.42-0.86%, which is significantly lower than the 1.45-3.26% of comparative examples 1-3. This indicates that the present invention, by using a carbon-boron-aluminum-yttrium composite sintering aid precursor in combination with boron carbide powder, can promote particle contact, grain boundary migration and pore discharge of recycled silicon carbide powder during the sintering process. This solves the problems of insufficient powder sintering activity, excessive residual porosity and low densification degree when recycling silicon carbide blank waste.

[0071] The three-point bending strength of Examples 1-3 was 421-462 MPa, which was significantly higher than that of Comparative Examples 1-3 (286-372 MPa). Specifically, Example 1 increased from 348 MPa to 462 MPa compared to Comparative Example 1 without the addition of the carbon-boron-aluminum-yttrium composite sintering aid precursor, compared from 372 MPa to 462 MPa compared to Comparative Example 2 without the addition of boron carbide powder, and compared from 286 MPa to 462 MPa compared to Comparative Example 3 without either addition. This indicates that the carbon-boron-aluminum-yttrium composite sintering aid precursor and boron carbide powder can jointly improve grain boundary bonding and green body sintering uniformity, and reduce the strength reduction of recycled waste ceramics caused by porosity, agglomeration, and weak grain boundaries.

[0072] The Vickers hardness of Examples 1-3 was 22.5-23.8 GPa, which was higher than that of Comparative Examples 1-3 (19.6-21.4 GPa), and the fracture toughness was 4.4-4.9 MPa·m. 0.5 It is higher than the 3.1-3.8 MPa·m of comparative examples 1-3. 0.5 This indicates that the silicon carbide ceramics prepared by this invention have improved hardness and crack resistance, solving the problems of insufficient hardness, low crack propagation resistance and large fluctuations in mechanical properties when simply recycling silicon carbide solid waste to prepare ceramics.

[0073] The wear rate of Examples 1-3 was 1.18 × 10⁻⁶. -6 -1.56×10 -6 mm 3 / (N·m), significantly lower than the 2.24×10 of comparative examples 1-3. -6 -3.85×10 -6 mm 3 / (N·m), among which Example 1 has the lowest wear rate, indicating that under the combined effect of higher bulk density, lower apparent porosity and higher hardness, the anti-abrasive ability of silicon carbide ceramic surface is enhanced, solving the problems of insufficient wear resistance, easy shedding of surface particles and poor use stability of existing silicon carbide solid waste recycled products.

[0074] Based on the comprehensive performance results, Examples 1-3, compared with Comparative Examples 1-3, demonstrate that this invention does not simply rely on the crushing and recycling of silicon carbide raw material waste. Instead, it achieves better dispersibility, formability, and sintering densification effects of recycled silicon carbide powder through the combination of a carbon-boron-aluminum-yttrium composite sintering aid precursor, boron carbide powder, water-soluble phenolic resin, and ammonium polyacrylate during the pulping, granulation, forming, and sintering processes. This realizes the high-value utilization of silicon carbide solid waste and solves the problems of low waste utilization rate, insufficient sintering density, decreased mechanical properties, and unstable wear resistance in the prior art.

Claims

1. A method for preparing silicon carbide ceramics using silicon carbide solid waste, characterized in that, Includes the following steps: S1. By weight, 490-510 parts of silicon carbide blank waste are crushed to obtain crushed silicon carbide blank waste; the crushed silicon carbide blank waste is placed in a heat treatment furnace and pre-degummed under air atmosphere, followed by degumming under nitrogen atmosphere, and naturally cooled to room temperature to obtain degummed silicon carbide waste. S2. Crush and classify the degummed silicon carbide waste to obtain silicon carbide powder; magnetically separate the silicon carbide powder to obtain recycled silicon carbide powder. S3. Add 85-95 parts of recycled silicon carbide powder, 1.0-3.0 parts of carbon-boron-aluminum-yttrium composite sintering aid precursor, 0.3-0.8 parts of boron carbide powder, 1.5-3.5 parts of water-soluble phenolic resin, 0.2-0.5 parts of ammonium polyacrylate and 45-60 parts of deionized water to a ball mill, ball mill, filter, and obtain silicon carbide ceramic slurry; S4. Spray granulation of silicon carbide ceramic slurry to obtain silicon carbide granulated powder; press silicon carbide granulated powder into shape to obtain a shaped green body; perform secondary debinding treatment on the shaped green body under nitrogen atmosphere, and then sinter it in argon atmosphere and cool it naturally to room temperature.

2. The method for preparing silicon carbide ceramics using silicon carbide solid waste according to claim 1, characterized in that, In step S1, the particle size of the crushed silicon carbide blank waste is 5-20 mm.

3. The method for preparing silicon carbide ceramics using silicon carbide solid waste according to claim 1, characterized in that, In step S1, the temperature for pre-degumming is 450-520℃, and the temperature for degumming is 750-850℃.

4. The method for preparing silicon carbide ceramics using silicon carbide solid waste according to claim 1, characterized in that, In step S2, the D50 of the recycled silicon carbide powder is 1.0-3.5μm.

5. The method for preparing silicon carbide ceramics using silicon carbide solid waste according to claim 1, characterized in that, In step S4, the temperature for the secondary degumming process is 500-650℃, and the sintering temperature is 2050-2150℃.

6. The method for preparing silicon carbide ceramics from silicon carbide solid waste according to any one of claims 1-5, characterized in that, The preparation steps of the carbon-boron-aluminum-yttrium composite sintering aid precursor include: A1. By weight, add 18.0-22.0 parts of yttrium hexahydrate, 26.0-30.0 parts of aluminum nitrate nonahydrate, 8.0-12.0 parts of boric acid, and 18.0-24.0 parts of citric acid monohydrate to a reactor, add 120-150 parts of deionized water, and stir at 55-65°C; then add 6.0-10.0 parts of glucose monohydrate and continue stirring; add ammonia water to adjust the pH to obtain a yttrium aluminum boron citric acid complex solution. A2. Cool the yttrium aluminum boron citric acid complex solution, add 80-110 parts of anhydrous ethanol dropwise, and continue stirring to obtain a gel precipitation system; allow the gel precipitation system to stand and age, filter, and obtain a wet precipitate; wash the wet precipitate with anhydrous ethanol to obtain a wet carbon boron aluminum yttrium composite precursor. A3. The wet carbon-boron-aluminum-yttrium composite precursor is dried at 80-90℃ to obtain a dried precursor; the dried precursor is crushed and sieved to obtain precursor powder; the precursor powder is placed in a tube furnace and heated to 320-380℃ under a nitrogen atmosphere, and then naturally cooled to room temperature to obtain carbon-containing intermediate powder. A4. Place the carbon-containing intermediate powder in a tube furnace and heat it to 620-700℃ under an argon atmosphere. Then, allow it to cool naturally to room temperature to obtain the activated product. Ball mill the activated product and sieve it.

7. The method for preparing silicon carbide ceramics using silicon carbide solid waste according to claim 6, characterized in that, In step A1, adjust the pH to 5.0-5.

4.

8. The method for preparing silicon carbide ceramics using silicon carbide solid waste according to claim 6, characterized in that, In step A2, the yttrium aluminum boron citric acid complex solution is cooled to 35-40℃; the aging time is 6-10 hours.

9. The method for preparing silicon carbide ceramics using silicon carbide solid waste according to claim 6, characterized in that, In step A3, the heating time to 320-380℃ is 1.0-1.5 hours.

10. The method for preparing silicon carbide ceramics using silicon carbide solid waste according to claim 6, characterized in that, In step A4, the treatment time for heating to 620-700℃ is 1.5-2.5 hours.